Analisis Pengaruh Economic Value Added (EVA), Return On Asset (ROA) Dan Return On Equity (ROE) Terhadap Market Value Added (MVA) - Luthfiyani Zahrah Alfairah; Palti Marulitua Sitorus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to find out the influence of EVA, ROA, and ROE on MVA both partially and simultaneously on companies listed in the highway, airport, port, and allied products sub-sector on the Indonesian Stock Exchange in 2017-2021. The sum of EVA, ROA, and ROE as free variables (independent), while MVA variables as bound variables dependent). The population in this study is listed in the Sub-sector of toll roads, airports, ports, and allied products on the Indonesia Stock Exchange from 2017-2021. Three companies used samples. The sampling technique used in this study was purposive sampling. The data analysis technique used is descriptive statistics. The results of the data obtained will be processed using IBM SPSS 26. Research results show that EVA partially has no significant relationship with MVA, while ROA and ROE have significant relationships with MVA. And EVA, ROA, and ROE simultaneously have no effect on MVA. The results of this study are expected to provide new knowledge to readers. Especially investors who will start investing are expected to pay attention to other factors besides EVA, ROA, and ROE. Keywords: Economic Value Added, Return On Assets, Return On Equity, Market Value Added, IBM SPSS 26